Benefits of using multiple Raman laser wavelengths for characterizing defects in a UO2 matrix. (27th February 2022) - Karcher, Samuel; Mohun, Ritesh; Olds, Travis; Weber, Marc; Kriegsman, Kyle; Zhao, Xiaodong; Guo, Xiaofeng; Corkhill, Claire; Field, David; McCloy, John
Abstract: Raman spectroscopy is one of the most useful techniques for studying the structure of UO2 and changes due to specific defects caused by doping, changes in stoichiometry, irradiation, or heating under oxidizing conditions. In this paper, we illustrate several aspects of the application of Raman techniques to the study of UO2, including the use of wavelength‐dependent excitation (455, 532, and 785 nm) to assess the effects of doping (Nd, Th, and Zr), ion irradiation, and in situ heating and oxidation (UO2 to U3 O8 ). Additionally, we show examples of how correlative microscopy is possible using electron backscatter diffraction combined with Raman maps of specific vibration bands or of laser‐induced luminescence generated by rare‐earth dopants in the matrix. For each of these applications, we suggest optimal excitation wavelengths that vary depending on the desired data. Blue (455 nm) excitation tends to promote oxidation even at low powers, but because Raman spectra change little with doping, irradiation‐induced changes are easier to observe. Green (532 nm) excitation is optimal for observing electron–phonon resonance effects in UO2 and offers a good compromise for high‐temperature oxidation experiments, delivering high‐quality spectra for both UO2 and U3 O8 . Infrared (785 nm) excitation is best for observing "defect" bands associated with doping in UO2, as changes with irradiation are small. Raman spectroscopy is particularly suited for studying the stability of UO2 towards oxidation in the presence of dopants simulating fission products, where electron–phonon resonant effects, dopant ion luminescence, and mapping can be used together to investigate structural rearrangement as a function of temperature. These techniques can offer insight into microstructural changes in UO2 fuels at higher burnups envisioned in future reactors. Abstract : Raman spectroscopy is very useful for studying the structural evolution of UO2 pellets that accumulate defects and fission product elements during and after use as nuclear fuel. Here, we illustrate spectroscopic differences obtainable with wavelength‐dependent excitation (455, 532, and 785 nm), for assessing effects of trivalent and tetravalent doping, ion irradiation, and in situ heating and oxidation (UO2 to U3 O8 ). We also show the benefits of mapping and correlative microscopy, including use of Raman laser‐induced luminescence of rare‐earth ions.